The contribution of fossils to chronostratigraphy, 150 years after Albert Oppel. (21st June 2017) - Balini, Marco; Ferretti, Annalisa; Finney, Stan; Monechi, Simonetta
Abstract : The 150th anniversary of the death of Albert Oppel (1831–65) provided the opportunity to celebrate this outstanding stratigrapher with a Thematic Issue dedicated to the importance of fossils for dating and correlating of sedimentary rocks. In this issue, we analyse Oppel's significant contribution to modern chronostratigraphy, before exploring the Phanerozoic through all its major fossil groups, to verify if fossils are still able to make a significant contribution to chronostratigraphy. The extraordinary merit of Oppel's work has been the demonstration that fossils can be used to sub‐divide sedimentary sequences into zones, which in turn might be organized in higher chronostratigraphical units. The zone for Oppel is characterized by the distinctive fossil content, and his view strongly influenced the development of the standard chronostratigraphical scale for about one century, until the introduction, in the 1950s, of the log‐based range chart as the common practice to study the fossil record of sedimentary successions. This approach forced the stratigraphers to shift the focus from the fossil content of the zones to their boundaries. This new view allowed for the introduction of new kind of zones with precisely defined boundaries based on bioevents and to the decline of the Oppel Zone. This turning point in the history of chronostratigraphy was fuelled by the International Commission on Stratigraphy programme of definition of the units of the International Chronostratigraphic Chart based on the boundary stratotype and point (GSSP) concept, which started in 1973.